Adjuvant systemic chemotherapy with or without bevacizumab in patients with resected pulmonary metastases from colorectal cancer - DANE, FAYSAL (WILEY-BLACKWELL, 2014)
Introduction: We investigated the impact of modern chemotherapy regimens and bevacizumab following pulmonary metastasectomy (PM) from metastatic colorectal cancer (CRC). Methods: A total of 122 consecutive patients who were curatively resected for pulmonary metastases of CRC in twelve oncology centers were retrospectively analysed between January 2000 and April 2012. Results: Of 122 patients, 14 did not receive any treatment following PM. The remaining 108 patients received fluoropyrimidine-based (n = 12), irinotecan-based (n = 56) and oxaliplatin-based (n = 40) chemotherapy combinations. Among these, 52 patients received bevacizumab (BEV) while 56 did not (NoBEV). Median recurrence-free survival (RFS) was 17 months and median overall survival (OS) has not been reached at amedian follow-up of 25 months after PM. Three and five-year OS rates were 66% and 53%, respectively. RFS and OS were similar, irrespective of the chemotherapy regimen or BEVuse. Positive pulmonary margin, KRASmutation status, and previous liver metastasectomy were negative independent prognostic factors for RFS, while pathologically confirmed thoracic lymph node involvement was the only negative independent prognostic for OS in multivariate analysis. Conclusions: No significant RFS or OS difference was observed in respect to chemotherapy regimens with or without BEV in patients with pulmonary metastases of CRC following curative resection.
Keywords: Adjuvant chemotherapy; bevacizumab; colorectal cancer; pulmonary metastasectomy; III COLON-CANCER; RANDOMIZED CONTROLLED-TRIAL; LUNG METASTASECTOMY; PHASE-III; PROGNOSTIC-FACTORS; K-RAS; BOLUS FLUOROURACIL; MUTATION STATUS; STAGE-II; OXALIPLATIN